Turning points in development thinking and practice - Louis Emmerij (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Why and when do turning points occur? How are they prepared? What are the choices before us when it comes to economic and social development policies? What is the role of culture in development? Do ideas play a role? What are the interests behind the ideas? The present paper tries to answer these and other questions and compares the advantages and disadvantages of global development theories with regional and local development policies that put more emphasis on the role of culture in economic development. – growth ; development ; global and local policies ; culture ; history ; ideas
Keywords: E1; E6; O1; 330; Entwicklungstheorie; Entwicklungspolitik